2021
DOI: 10.3390/fermentation7030157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreated Colza Straw on the Growth and Extracellular Ligninolytic Enzymes Production by Lentinula edodes and Ganoderma lucidum

Abstract: Lentinula edodes 3565 and Ganoderma lucidum 9621 were compared for their ability to produce lignocellulolytic enzymes in submerged (SM) and surface liquid (SL) fermentation of hydrolysed colza straw lignin waste that remained after the production of furfural and bioethanol (CS lignin). Application of cultivated mushrooms to dispose of pretreated colza straw agricultural waste is an approach to decrease the quantity of residual lignin while simultaneously obtaining active substances, e.g., the ligninolytic enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…This corresponds to approximately two quarters of colonization (30 days), with a decrease in enzymatic activity at the end of the fermentation period. Makarenkova et al (2021) found that G. lucidum reached higher laccase production on the 14 th day of cultivation (550 U/mL) when using colza straw lignin as a substrate.…”
Section: Resultsmentioning
confidence: 94%
“…This corresponds to approximately two quarters of colonization (30 days), with a decrease in enzymatic activity at the end of the fermentation period. Makarenkova et al (2021) found that G. lucidum reached higher laccase production on the 14 th day of cultivation (550 U/mL) when using colza straw lignin as a substrate.…”
Section: Resultsmentioning
confidence: 94%